Mesa redonda: Módulo Quirúrgico - Cardemil, Gonzalo; Spence, Richard; Shander, Aryeh; Cohn, Stephen; Navarrete, Claudio; Trainini, Jorge (Revista Hospital Clínico Universidad de Chile, 2000)
Resumen no disponible